2016
DOI: 10.1515/les-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Contextualising Translator Training: Defining Social, Professional and Disciplinary Requirements

Abstract: In order to adapt universities to the social, disciplinary and professional needs, we consider it necessary to contextualise the professional profiles of translators. The main groups involved in the educational process are translation teachers and researchers, employers and students/graduates, and their contribution to the definition of professional profiles is essential. Therefore, in this article we will focus on studies about professional profiles from the following perspectives: translation market studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In Western countries, for example, Plaza-Lara (2018 found that "the competences promoted in translation project management in EMT courses seem to be aligned with those proposed by the professional sector". However, in the East, particularly in Greater China, project management and interpersonal skills are often not present in translation curricula, which tend to focus on teaching translation skills.…”
Section: Project Management Competencesmentioning
confidence: 99%
“…In Western countries, for example, Plaza-Lara (2018 found that "the competences promoted in translation project management in EMT courses seem to be aligned with those proposed by the professional sector". However, in the East, particularly in Greater China, project management and interpersonal skills are often not present in translation curricula, which tend to focus on teaching translation skills.…”
Section: Project Management Competencesmentioning
confidence: 99%
“…Sus líneas de investigación principales son la didáctica de la traducción, las tecnologías educativas y la enseñanza de lenguas para traductoras/es en formación. La académica cuenta con numerosas publicaciones sobre formación y desarrollo de competencias traductológicas (Lara, 2016;Plaza-Lara, 2021) o el papel de la posedición (Plaza-Lara, 2020). En lo que concierne a la TAD, se ha centrado en la AD didáctica (Plaza Lara & Gonzalo Llera, 2022b) y el subtitulado didáctico (Plaza Lara & Fernández Costales, 2022).…”
Section: Cristina Plazaunclassified
“…Similarly, more and more scholars support the idea of aligning university training with market needs(Plaza-Lara 2016;Gabr 2007;Olohan 2007), as the latter sets the standard andtransLogos 2022 Vol 5 Issue 1 Peña Aguilar, Argelia, pp. 43-65 Alignment of Translation Technology Training with Professional Practice in Mexico: A Glimpse into the Situation the pace in the field, and it may provide input for the improvement of any training curriculum or syllabus.…”
mentioning
confidence: 99%